The Evaluation of Teaching Factory Implementation in Pika Industrial Wood Working School Semarang by Using Cipp Approach - Kuntjoro, Yoh. Sasmito; Sutopo, Yeri; Hudallah, Noor; Syamwil, Rodia (Journal of Vocational and Career Education, 2021)
The Teaching Factory (TeFa) learning model is a learning model used in aproduction or service-based vocational school that refers to standards,procedures, and an industry-like atmosphere (companies). PIKA IndustrialWood Working School Semarang is one of the vocational schools thatimplements the TeFa learning model. The implementation of ongoing TeFalearning requires evaluation so that the program can run according to theexpected goals. The evaluation of the TeFa learning implementation used theCIPP evaluation model which consists of four aspects; they are Context, Input,Process, and Product (CIPP). This study aims to determine the extent of theimplementation of TeFa learning in terms of the four aspects by usingquestionnaires, interviews, observations, and documentation. The observationresults of the teachers and industry representatives in terms of Context, Input,Process, and Product aspect showed that the implementation of TeFa learningwas considered in the very good category in accordance with the standards setby the Directorate of Vocational Education of Indonesian Ministry ofEducation, Culture, Research, and Technology with the achievement result of93% context, 96.2% inputs, 91.4% process, and 84.6% product. The results alsoshowed that the implementation of TeFa learning, according to the teacher, interms of Context, Input, Process, and Product aspects was included in the verygood category, with the respective achievements of 91.8%, 95%, 92.9% and93.4%. In addition, according to the students, the implementation of TeFalearning in terms of Context, Input, Process, and Product aspect was includedin the very good category, with the achievements of 82.8%, 89%, 89%, and93.8% respectively.